Ultimate shear capacity and failure of shear key connection in precast concrete construction - Ibrahim, Izni Syahrizal (2014)
This paper presents the experimental results on the strength of shear key connection in precast concrete construction. The use of shear key is to connect two separate precast components to increase the shear resistivity of the joint surfaces. The proposed shear key shape in this study comprises of triangular, composite rectangular, semi - circle and trapezoidal. In addition, the trapezoidal shape is made up with 3 different key’s angles. All specimens are tested using the “push - off” method to obtain the ultimate shear capacity of which is due to the failure of the connection. From the analysis, stiffness, elastic and plastic behaviour, and the mode of failure is discussed to determine the most effective shape of the proposed shear key. From the findings, semi - circle shear key produced the highest shear capacity at 62.9 kN compared to that of the other shapes. Meanwhile, the trapezoidal shape at an angle of 45° produced the highest shear capacity at 44.1 kN. Together in the aspect of stiffness,the 45° trapezoidal shapes produced the highest resistance towards slip at 166.7 kN/mm. Failure mode are mostly due to shear, sliding and diagonal tension crack. Large slip of 7.35 mm is recorded from the triangular shape. The large slip is maybe due to sliding since the angle of the key faces to the shear plane is 45° which indicates to less interlocking compared with the other shapes they form an angle of 90° with the shear plane.